Development Clothing Information System base Android Applications of Boutique Modiste Shofi Samarinda - Nani Wijaya; Yulianto; Budi Rachmadani (TEPIAN, 2022)
WEB-Based Development of Apparel Information Systems at Shofi Boutique Samarinda. using Laravel Framework. The Modiste Shofi Boutique is a boutique that sells various types of men's and women's clothing. The clothes sold at the Modiste Shofi Boutique include mukena, batik clothes, batik cloth, and so on. The promotions carried out by the Modiste Shofi Boutique are still inadequate so that there are still many people who do not know the existence of the Modiste Shofi Boutique. In addition, sales at the Modiste Shofi Boutique are only done manually such as promoting goods on Facebook and Whatsapp only, and also conventionally where consumers have to come directly to the Modiste Shofi Boutique to buy clothes, therefore this research the author did to create this application that can facilitate the promotion of clothing and can do promotions widely so that consumers are easier to transact and do not need to come to the boutique. This application also aims to make it easier for Modiste Shofi Boutique owners to record goods and be able to view detailed sales and purchase reports at Modiste Shofi Boutique Samarinda